PERAN DINAS SOSIAL DAN PEMAKAMAN KOTA PEKANBARU DALAM MENANGANI ANAK TERLANTAR TAHUN 2013 - Chandra Rizal; Raja Muhammad Amin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
63277The role of the state in providing services to the community should be based on the basic values of Pancasila social justice for all Indonesian people, including in reducing social welfare issues. under the Act of 1945 in Article 34 Paragraph 1 mentioned the poor and neglected children who are maintained by the state, with this Government Pekanbaru Pekanbaru City Regional Regulation No. 12 Year 2008 concerning the social order in which the regulation is described in Chapter 1 Article 1 Paragraph 20, which reads